Systemic lupus erythematosus and Klinefelter's syndrome. - French, M A (1983)
A case of Klinefelter's syndrome presenting with systemic lupus erythematosus while receiving androgen replacement therapy is described. The association of systemic lupus erythematosus with Klinefelter's syndrome is discussed, particularly in terms of the effect of sex hormones.